Systematic Literature Study on the Role of Islamic Economics in Sustainable Economic Development - M Hikam Fauzan Arifin; Moch Chotib; Ahmadiono Ahmadiono (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the role of Islamic economics in supporting sustainable economic development through the Systematic Literature Review (SLR) approach. The SLR method is used to systematically identify, evaluate, and synthesize relevant literature on the contribution of Islamic economics to the sustainable development goals (SDGs). The review process begins with formulating the main research question, as well as establishing inclusion and exclusion criteria that include publications between 2020 and 2025, available in full-text form, and focusing on Islamic economics and sustainability issues. The results of the study show that Islamic economics is closely related to the principles of sustainability, such as justice, balance, social responsibility, and the prohibition of detrimental economic practices. Islamic economic instruments such as zakat, infaq, sedekah, waqf, and sharia-based financing play an important role in creating an inclusive, fair, and social welfare-oriented economic system. In addition, Islamic banks and Islamic social finance also encourage sustainable financing of the real sector and MSMEs, including through innovations such as green sukuk and productive waqf. Thus, sharia economics has proven to be a strategic and applicable framework in realizing fair, inclusive and sustainable economic development